Pengaruh Kelengkapan Produk dan Lokasi Terhadap Minat Beli Konsumen Pada Giant Expresss Sukabumi : Studi Kasus konsumen Giant Expresss Sukabumi - Ryan Kurniawan; Yuniar Aisah Krismonita (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2020)
Retailing is the entire business activity associated with selling and providing services to end consumers. The retail business in Indonesia is progressing well which is always followed by very intense competition between companies. Although retail sales are on the rise, according to the financial statements for 2018 PT. Hero Supermarket Tbk shows a decline and loss is supported by the closing of several Giant Express stalls in various cities. As such, this study aimed to determine whether product completeness and location influenced the buying interest in Giant Express supermarkets. A total of 100 respondents were surveyed, using the purposive sampling method. The data analysis techniques used in this study are validity test, reliability test, classical assumption test, descriptive and hypothesis test. The results show that 1) Product completeness has a partial and significant effect on Consumer Buy Interest, 2) Location has a significant and significant effect on Consumer Buy Interest, and 3) Product completeness and Location Equity has a significant impact on Consumer Buy Interest.